PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MEMBANGUN INTERAKSI SOSIAL PESERTA DIDIK KELAS VIII DI SMP NEGERI 8 DENPASAR - Ni Kadek Sri Diantari; Ni Made Muliani; I Made Nasib Mardika (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the implementation of the Jigsaw-type Cooperative Learning model in Hindu Religious Education and Character Education classes to foster social interaction among eighth-grade students at SMP Negeri 8 Denpasar. The study employed a qualitative descriptive research design. Data were collected through classroom observations, in-depth interviews, and documentation. The research participants consisted of Hindu Religious Education teachers, eighth-grade students, and relevant school stakeholders involved in the learning process. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the Jigsaw model was carried out through the formation of home groups and expert groups, collaborative discussions, peer teaching activities, and learning evaluation. The model enhanced students’ active participation, individual responsibility, and engagement during classroom activities. Social interactions developed predominantly in associative forms, including cooperation, accommodation, assimilation, and acculturation, while dissociative interactions such as competition and contravention appeared at a low level and remained constructive. The study concludes that the Jigsaw Cooperative Learning model is effective in fostering positive social interaction, communication skills, collaborative learning experiences, and meaningful participation in Hindu Religious Education and Character Education classes.